Rational Design and Lead Optimisation of Potent Antimalarial Quinazolinediones and Their Cytotoxicity against MCF-7 - Sitthivut Charoensutthivarakul; Duangporn Lohawittayanan; Phongthon Kanjanasirirat; Kedchin Jearawuttanakul; Sawinee Seemakhan; Napason Chabang; Patrick Schlaeppi; Varisa Tantivess; Tanapol Limboonreung; Matthew Phanchana (My University, 2023)
Quinazolinedione is one of the most outstanding heterocycles in medicinal chemistry thanks to its wide ranges of biological activities including antimalarial, anticancer, and anti-inflammatory. TCMDC-125133 containing a quinazolinedione pharmacophore displays promising antimalarial activity and low toxicity, as described in the GlaxoSmithKline (GSK) report. Herein, the design and synthesis of novel quinazolinedione derivatives is described on the basis of our previous work on the synthesis of TCMDC-125133, where low-cost chemicals and greener alternatives were used when possible. The initial SAR study focused on the replacement of the valine linker moiety; according to the in silico prediction using SwissADME, concise four-step syntheses toward compounds 4-10 were developed. The in-house synthesized compounds 4-10 were assayed for antimalarial activity against P. falciparum 3D7, and the result revealed that only the compound 2 containing a valine linker was tolerated. Another round of lead optimization focused on the replacement of the m-anisidine moiety in compound 2. A library of 12 derivatives was prepared, and the antimalarial assay showed that potent antimalarial activity could be maintained by replacing the methoxy group in the meta position of the phenyl side chain with a fluorine or chlorine atom (21: IC50 = 36 ± 5 nM, 24: IC50 = 22 ± 5 nM). Further lead optimization is underway to enhance the antimalarial activity of this class of compound. The compounds included in the study possess little to no antiproliferative activity against MCF-7 cells.
Keywords: Moiety; Lead compound; Linker; Rational design; IC50; Antimalarial Agent; Quinazolinone synthesis and applications